Research on the Reinforcement Mechanism and Safety Monitoring of Heavy-Duty Concrete-Encased CFST Columns - Xiu-Hua Guo; Jin-Feng Jiao; Zhi-An Wu; Jian-Li Zhang (Advances in Civil Engineering)
With the reinforcement project of a heavy-duty concrete-encased concrete-filled steel tube (CFST) column as the background, the mechanism of column reinforcement with supporting beams is proposed. The key mechanisms include the following: (1) designing the upper and lower corbel-shaped temporary support columns, (2) crack repairing the inner steel pipe using patch-shaped steel plates, and (3) replacing microwound concrete inside the steel pipe, which are all innovative and effective methods. Moreover, a system is developed for monitoring the safety during the reinforcement process and recovering the bearing capacity of the concrete-encased CFST column. The monitoring results indicate that the load conversion process of the temporary support columns lasts for 50 days, that the sum of the axial forces of the four supporting columns is 7,966.0 kN, accounting for 65% of the standard load, and that during the whole process, the structural components are safe and reliable. Finally, the construction simulation is in agreement with the field test results, which proves that the construction simulation developed based on the theory of slow time-dependent mechanics and the method of static nonlinear analysis is accurate.